2013
DOI: 10.1007/s10900-013-9791-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity and Eating in the Absence of Hunger Among College Students in a Mexican-USA Border City

Abstract: Few studies have examined disinhibited eating behaviors in Mexico. However eating in the absence of hunger (EAH), defined as eating in response to the presence of palatable foods in the absence of physiological hunger, is one of the more frequently examined behaviors. The purpose of this study was to assess the association between obesity and EAH among college students in a large Mexican-USA border city. Two-hundred and one sophomore college students completed the EAH questionnaire (EAH-C). Weight and height w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Whereas excessive food restriction and control disrupts children’s recognition of their internal hunger and satiety cues [2, 4, 8, 9], following a feeding dynamic approach is theorized to enhance children’s attention to these cues, which should, in turn, help prevent their eating in the absence of hunger [1]. Eating in the absence of hunger (EAH), a research procedure used to determine satiety responsiveness is defined as eating in response to the presence of palatable foods in the absence of physiological hunger” [10, 11]. Children who eat in the absence of hunger have higher BMIs and a greater likelihood of becoming obese [2].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas excessive food restriction and control disrupts children’s recognition of their internal hunger and satiety cues [2, 4, 8, 9], following a feeding dynamic approach is theorized to enhance children’s attention to these cues, which should, in turn, help prevent their eating in the absence of hunger [1]. Eating in the absence of hunger (EAH), a research procedure used to determine satiety responsiveness is defined as eating in response to the presence of palatable foods in the absence of physiological hunger” [10, 11]. Children who eat in the absence of hunger have higher BMIs and a greater likelihood of becoming obese [2].…”
Section: Introductionmentioning
confidence: 99%
“…These results would provide relevant information to universities offering this undergraduate curriculum to identify applicants in which is necessary to increase physical activity levels or make decisions about interventions to avoid potentially risky behaviors while reducing the risk of metabolic syndrome. Pérez-Morales et al [ 40 ] reported that eating disorders are associated with variables such as boredom, sadness and depression besides the accumulation of adipose tissue, increasing overweight and obesity prevalence. In this regard, school managers should consider their monitoring and prevention activities in college students.…”
Section: Discussionmentioning
confidence: 99%
“…Within these, the scale includes three motivators of eating in the absence of hunger: Negative affect (feeling sad or depressed, angry or frustrated, anxious or nervous); external eating (e.g., food looks, tastes or smells good and/or being in the presence of others who are eating); and fatigue/boredom. EAH‐C was originally developed and validated for children and adolescents 24 but modified for college students and found to have high internal consistency across subscales (0.83–0.92) 25 . In a subset of participants ( n = 1162 [30.5%] WLM and 139 [26.8%] controls), the Diet History Questionnaire (DHQ‐II) from the National Institutes of Health was used to measure self‐reported calorie and macronutrient intake 26 .…”
Section: Methodsmentioning
confidence: 99%
“…EAH-C was originally developed and validated for children and adolescents 24 but modified for college students and found to have high internal consistency across subscales (0.83-0.92). 25 In a subset of participants (n = 1162 [30.5%] WLM and 139 [26.8%] controls), the Diet History Questionnaire (DHQ-II) from the National Institutes of Health was used to measure self-reported calorie and macronutrient intake. 26 The DHQ-II was included as an exploratory and optional measure in the WWSR.…”
Section: Methodsmentioning
confidence: 99%